Effectiveness of icatibant for treatment of hereditary angioedema attacks is not affected by body weight: findings from the Icatibant Outcome Survey, a cohort observational study. Issue 1 (23rd March 2018) - Caballero, Teresa; Zanichelli, Andrea; Aberer, Werner; Maurer, Marcus; Longhurst, Hilary J.; Bouillet, Laurence; Andresen, Irmgard; ,; Aberer, W.; Wiednig, M.; Grumach, A.; Bygum, A.; et al.
Abstract: Background: Icatibant is a bradykinin B2‐receptor antagonist used for the treatment of hereditary angioedema attacks resulting from C1‐inhibitor deficiency. Treatment is not adjusted by body weight however the impact of body mass index (BMI) on the effectiveness of icatibant is not documented in the literature. We examined disease characteristics and icatibant treatment effectiveness in patients stratified by BMI in the Icatibant Outcome Survey, an ongoing, international, observational study monitoring the real‐world safety and effectiveness of icatibant. Methods: Attack and treatment characteristics as well as outcomes following treatment with icatibant were compared among patients with underweight, normal, overweight, and obese BMI. Results: Data from 2697 icatibant‐treated attacks in 342 patients (3.5, 44.7, 34.8, and 17.0% patients of underweight, normal, overweight, and obese BMI, respectively) were analyzed. There was no significant difference in the frequency and severity of attacks across BMI groups, although obese patients tended to have more attacks of high severity. There was no impact of BMI on the frequency of laryngeal attacks, but patients with normal BMI had fewer cutaneous attacks and more abdominal attacks. Most attacks (71.9–83.8%) were treated with a single icatibant injection without the need for rescue with plasma‐derived C1‐inhibitor (pdC1‐INH), regardless of BMI. Patients with obese BMI used pdC1‐INH as rescue treatment more often (P < 0.0001; P = 0.0232 excluding 2 outliers) and treated attacks earlier than patients with normal BMI (P = 0.007). Furthermore, time to resolution and duration of attack were shorter for patients with high BMI (P < 0.001 for overweight and P < 0.05 for obese versus normal). Conclusion: Overall, icatibant was comparatively effective in treating attacks in patients across all BMI groups. Trial registration NCT01034969.